Sentencing scorecards: reducing racial disparities in prison sentences at their source - Ridgeway, Greg (Criminology & public policy, 2020)
Research Scorecards have become an increasingly common tool for public policy decision making about important issues in education, finance, and health care. Few scorecards have been applied in criminal justice and none has been developed to highlight racial disparities in incarceration. We constructed county-level scorecards for racial disparities in incarceration rates for the New York State Permanent Commission on Sentencing. Using detailed data on felony cases in New York State between 2000 and 2014, including the specific penal law criminal offense, features of the underlying charges, and criminal history, we assembled a set of White defendants within each county that collectively resembled Black and Hispanic defendants in that county. Statewide, Black defendants were more likely to receive prison sentences than similar White defendants (43% vs. 40%). Some individual counties had much greater racial disparities with relative risks of prison as high as 1.36. We found similar results for Hispanic defendants. Policy Implications Early institutional support for our scorecard receded once racial disparities were flagged in specific, named counties. The scorecard was never deployed by the Commission. Commission members and the research team met with individual counties but the Commission was disbanded during this process. New York State still lacks a formal sentencing commission. We recommend future scorecard efforts come from legislative or executive mandates, requiring rigorous methods and public presentations.